Eye of the storm : chasing storms with Warren Faidley - Kramer, Stephen P. (New York : G.P. Putnam$1 (Bs Sons,s, 1997)
Storm chaser Warren Faidley discusses the techniques, dangers, and difficulties of photographing lightning, tornadoes, and hurricanes.
Includes bibliographical references (p. 48).
Keywords: Faidley, Warren; Faidley, Warren; Storms -- Juvenile literature; Storms -- Pictorial works -- Juvenile literature; Photography -- Scientific applications -- Juvenile literature; Storms; Photography